Pain sensitivity as a state marker and predictor for adolescent non-suicidal self-injury - Kao, Han-Tin; Mürner-Lavanchy, Ines M.; Stosch, Elisabeth von; Josi, Johannes; Berger, Thomas; Koenig, Julian; Kaess, Michael (Psychological medicine, 2024)
BackgroundThe pain analgesia hypothesis suggests that reduced pain sensitivity (PS) is a specific risk factor for the engagement in non-suicidal self-injury (NSSI). Consistent with this, several studies found reduced PS in adults as well as adolescents with NSSI. Cross-sectional studies in adults with borderline personality disorder (BPD) suggest that PS may (partially) normalize after remission or reduction of BPD symptoms. The objective of the present study was to investigate the development of PS over 1 year in a sample of adolescents with NSSI and to investigate whether PS at baseline predicts longitudinal change in NSSI.MethodsN = 66 adolescents who underwent specialized treatment for NSSI disorder participated in baseline and 1-year follow-up assessments, including heat pain stimulation for the measurement of pain threshold and tolerance. Associations between PS and NSSI as well as BPD and depressive symptoms were examined using negative binomial, logistic, and linear regression analyses.ResultsWe found that a decrease in pain threshold over time was associated with reduced NSSI (incident rate ratio = 2.04, p = 0.047) and that higher pain tolerance at baseline predicted lower probability for NSSI (odds ratio = 0.42, p = 0.016) 1 year later. However, the latter effect did not survive Holm correction (p = 0.059). No associations between PS and BPD or depressive symptoms were observed.ConclusionOur findings suggest that pain threshold might normalize with a decrease in NSSI frequency and could thus serve as a state marker for NSSI.
Gesehen am 12.07.2024